Political Dynamics and Conflict of Interest in the Implementation of Jakarta Government Policies for the 2017-2018 Period - Eddy Guridno; Aberar Guridno (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Political dynamics and conflicts of interest play a significant role in shaping local government policies, especially in urban areas with diverse stakeholders. The closure of Alexis Hotel and Alexis Massage Griya in Jakarta (2017–2018) is a key example of how public policy intersects with political conflict, interest group mobilization, and governance legitimacy. Objective: This study aims to analyze the DKI Jakarta Regional Government's policy on the closure of Alexis, exploring the motivations behind the policy, the responses of interest groups and political factions, and the impact of the political conflict that arose from this decision. Methods: A qualitative case study approach was used, involving in-depth semi-structured interviews, document analysis, and observation of DPRD sessions. The data were analyzed using thematic coding, focusing on political conflict theory and public policy theory to explain the underlying dynamics. Results: The study finds that the closure was influenced by campaign promises, the moral preferences of the governor and deputy governor, public support, and regulations. Political conflict arose from differing views on life, political elites' desire to maintain legitimacy, and inter-coalition conflicts. The policy led to fairer law enforcement, fewer regulatory manipulations, increased popularity for the DKI Regional Government, and similar cases in Jakarta. Conclusion: The closure of Alexis Hotel was driven by moral preferences, political legitimacy, and legal considerations. The conflict within the DPRD arose from differing worldviews and political interests. This study enhances political conflict theory by emphasizing worldview differences and the influence of national politics on local conflicts.